Using Augmented Reality to Enhance and Engage Students in Learning Mathematics - Chao, Wen-Hung; Chang, Rong-Chi (Advances in Social Sciences Research Journal, 2019)
The study shall apply Augmented Reality (AR) technique to develop Math learning App. The learners shall apply the mobile device to scan the cards and convert the 2D floor plan into 3D objects. By manipulating virtual 3D objects, students can understand the 3D composition from different perspectives. By applying the decomposition or combinated functions of the Math learning App, students can further understand the calculation way of Volume. The study confers the learning outcomes of the school children before and after applying AR Math App through the introduction and experiment design of the teaching site, and discusses the difference between Math high-accomplished school children and ordinary children by way of digital learning. Through the ways of achievement tests, questionnaire and teachers’ and childrents’ interviews, the study understands the learning effects and experiencing of AR Math App. The experiment’s result indicates that students can accept the AR Math learning App developed by the institute and it can also initiate their interests in learning. The result before and after studying indicates that the learning effects have significantly promoted. The result of teachers’ interviews indicate that the application of this digital teaching materials and interactive experience model has effectively enhanced the students understanding the concept of Volume and 3D composition.